Minstrelsy, Apprenticeship, Origin and Features of Biripo, the Ilaje Folk-Poetry - Stephen Ola Ajimisan (Randwick International of Social Science Journal, 2023)
Issues of minstrelsy, apprenticeship, origin, features of Biripo, the Ilaje oral performance in chanting and singing modes, and the influence of modernity and technology on it have never been subjects of any known research in folkloric literature or other fields of human knowledge. This paper thus, investigates the issues of minstrelsy, apprenticeship in Biripo, origin and features of Biripo among the people. The paper employs sociological approach to the study of Biripo since it operates within its society of origin. Sociological approach to the study of literature or folklore examines a text or indigenous oral performances through sociological binoculars with a view to examining how the text has been influenced by the society and vice-versa which justifies the adoption of the theory. The paper also gathers information through oral interviews and secondary materials such as textbooks, journal articles and cyber materials. The research finds out that: the issues of minstrelsy, apprenticeship is present in Biripo the way it is in other indigenous forms, the oral (Biripo) artist occupies special place in his community and enjoys special privilege from the community leaders and the people, Biripo is a product of the people’s tradition and quotidian existence from the pre-literate and post-literate eras and that modernity and technology have tremendously influenced Biripo, functional application and that the use of ideophones, call and response, affinity with ritual and masquerades songs etc are features of Biripo. The paper advocates the technologising of Biripo for the 21st century exigencies and realities.